2021
DOI: 10.3390/ijms22042150
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Clinical Outcomes of CAR T-Cell Therapies for B-Acute Lymphoblastic Leukemia

Abstract: Introduction: Treatment of relapsed and refractory (R/R) B acute lymphoblastic leukemia (B-ALL) represents an unmet medical need in children and adults. Adoptive T cells engineered to express a chimeric antigen receptor (CAR-T) is emerging as an effective technique for treating these patients. Areas covered: Efficacy and safety of CAR-T therapy in R/R B-ALL patients. Expert opinion: CD19 CAR-T infusion induce high CR rates in patients with poor prognosis and few therapeutic options, while real-life data demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 78 publications
1
54
0
1
Order By: Relevance
“…This set of patients usually receives additional chemotherapy cycles and possibly hematopoietic progenitor transplants, which are frequently ineffective [12]. It is in this group of highly treated patients that a good rate of response to CAR T therapy has been observed [13]. Clinical trials have shown that CAR T-cells are able to expand in vivo, eliminate leukemia burden, and persist in the patient for as long as two years [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This set of patients usually receives additional chemotherapy cycles and possibly hematopoietic progenitor transplants, which are frequently ineffective [12]. It is in this group of highly treated patients that a good rate of response to CAR T therapy has been observed [13]. Clinical trials have shown that CAR T-cells are able to expand in vivo, eliminate leukemia burden, and persist in the patient for as long as two years [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We focused on CARs that contain a CD28+CD3z endodomain since CD19 expression is most commonly retained at the time of disease relapse, following infusion of these cells (16)(17)(18). To generate a panel of scFvs with varying ability to bind CD19, CDR3 of the V H domain within the CD19-specific FMC63 scFv was subjected to alanine scanning mutagenesis (Figure 1A).…”
Section: Generation Of a Panel Of Fmc63 Modified Cars With Specificit...mentioning
confidence: 99%
“…Moreover, greater than 50% of patients who receive CD19-specific CAR T-cell immunotherapy ultimately develop progressive disease (15). Relapse in which CD19 expression is maintained is the most common scenarioparticularly with CD28-containing 2G CARs -and this has been linked to limited persistence of CAR T-cells (16)(17)(18). Given the need for more potent and durable CAR T-cell strategies to target CD19, we set out here to develop CD19-targeted pCARs in order to test their potential utility in models of B-cell malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…На аутопсии пациента Б-к в костном мозге обнаружено небольшое количество бластов в состоянии некробиоза, несмотря на то, что он умер на 10-е сутки от введения CAR-T-клеток. Высокую антилейкемическую активность CAR-T-клеток отмечают многие исследователи [9,10] даже после неудачной терапии ОЛЛ блинатумомабом [8].…”
Section: таблицаunclassified